Cuticular study of Bennettitales from the Springhill Formation, Lower Cretaceous of Patagonia, Argentina - Villar, Liliana Monica (Cretaceous Research)
Cuticles of leaves and scale-leaves belonging to the order Bennettitales are discussed using light microscopy (LM) and scanning and transmission electron microscopy (SEM and TEM). The cuticles occur in the Springhill Formation (Lower Cretaceous) of Santa Cruz Province, Argentina. The fossil group is represented by seven species of which one is new and three other species have their diagnosis emended by ultrastructural analysis. The species studied are Otozamites patagonicus sp. nov., Otozamites archangelskyi Baldoni and Taylor, 1983, Pterophyllum trichomatosum Archangelsky and Baldoni, 1972, Ptilophyllum valvatum Villar de Seoane, 1995, Ptilophyllum antarcticum (Halle) Archangelsky and Baldoni, 1972, Cycadolepis coriacea Menéndez, 1966 and Cycadolepis involuta Menéndez, 1966. The leaves and scale-leaves show xeromorphic characters such as sculptured surfaces, sunken stomata and a thick external wall in the epidermis. The xeromorphic characters could indicate high temperatures, low humidity and arid soils. These palaeoenvironmental conditions may have been associated with volcanic activity. The presence of carbonized specimens also suggests the development of forest fires produced by dry seasonal conditions or regional volcanic activity. Fil: Villar, Liliana Monica. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina